Novel mouse model of indwelling pleural catheter in mice with malignant pleural effusion - Merrick, C; Sherrill, T; Kanellakis, N; Asciak, R; Stathopoulos, G; Maldonado, F; Rahman, N; Blackwell, T; Psallidas, I (European Respiratory Society, 2019)
This novel mouse model mimics malignant pleural effusion drainage using an indwelling pleural catheter in humans, and provides direct access to the pleural space potentially enabling the testing of intrapleural therapies in the treatment of MPE. bit.ly/2W2kzO0.